Perubahan Histopatologis Saluran Pencernaan Dan Otak Pada Unggas Yang Terinfeksi Virus Avian D Influenza Yang Dikoleksi Ari Laboratorium Patologi, Balai Besar Veteriner Wates,Yogyakarta - MUHAEMINAH, Abdah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The implementation of job training is to conduct a field trip study that was at the Disease Investigation Center (DIC), Wates Yogyakarta. The aim of the present field trip study was to get insight and comprehensive knowledge, especially in regard to the poultry diseases e.g. avian influenza virus (AIV). The data based on the positive AIV gastrointestinal and the brains infected-chickens during 2010, 2011 and 2012 were collected from the DIC, Wates, Yogyakarta. The gastrointestinal tract and the brains were processed histopathologically and stained with a routine stain of hematoxylin-eosin to definitely confirm the diagnosis that are based on clinical signs. The data collected indicated that all the gastrointestinal tract and the brains had histopathologic lesions, such as moderate to severe, diffuse multifocal hemorrhages.